Four-mold anti-counterfeiting glass as well as preparation method and application thereof

A four-mode anti-counterfeiting glass with SiO2, Na2CO3, Al2O3, CaCO3, NaF, LuF3, and EuF3 composition addresses the limitations of single-mode anti-counterfeiting by providing multiple secure, stable, and environmentally friendly modes, suitable for industrial use.

CN119176671AActive Publication Date: 2024-12-24YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411365021.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

Existing anti-counterfeiting materials often rely on single modes that are easily imitated, require multiple materials increasing cost and complexity, and may have stability and environmental issues, limiting their practical application.

Method used

A four-mode anti-counterfeiting glass utilizing SiO2, Na2CO3, Al2O3, CaCO3, NaF, LuF3, and EuF3 with a Eu 2+/Eu 3+ luminous center, offering fluorescent, long afterglow, light stimulation, and heat stimulation modes, prepared through controlled melting and heat treatment processes.

Benefits of technology

The glass provides high security, stability, cost-effectiveness, and flexibility, with adjustable luminescent properties suitable for industrial production and easy recycling, enhancing anti-counterfeiting capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176671A_ABST
    Figure CN119176671A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical function materials and display, and discloses four-mode anti-counterfeiting glass, a preparation method and application of the four-mode anti-counterfeiting glass in the anti-counterfeiting field. The glass comprises the following components in molar ratio: 30 to 60 mol percent of SiO2, 5 to 20 mol percent of Na2CO3, 5 to 30 mol percent of Al2O3, 3 to 10 mol percent of CaCO3, 3 to 20 mol percent of NaF, 3 to 20 mol percent of LuF3 and 0 to 5 mol percent of EuF3. The four-mode anti-counterfeiting glass has four anti-counterfeiting modes of fluorescent light emitting color, long afterglow light emitting color, long afterglow recovery through light stimulation and long afterglow recovery through thermal stimulation, and Eu < 2 + > / Eu < 3 + > is taken as a light emitting center. The preparation method comprises the steps of accurately weighing raw materials, fully mixing, adding reducing agent powder, melting in a high-temperature smelting furnace, casting a mold, quenching, cutting and polishing, treating in a low-temperature furnace and the like. The invention is used in the anti-counterfeiting field, and has the advantages of low cost, high stability, high luminous efficiency, adjustable shape, environmental friendliness and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optoelectronic functional materials and anti-counterfeiting technology, and specifically to a four-mode anti-counterfeiting glass, a preparation method and application thereof. Background Art

[0002] With the rapid development of information technology and the globalization of commodity markets, the problem of counterfeiting and illegal duplication of goods has become increasingly serious. The proliferation of counterfeit products not only infringes on the rights and interests of brand owners, but also threatens the safety of consumers and the normal order of the market. Traditional anti-counterfeiting strategies such as watermarks and barcodes are easy to copy and cannot meet the growing anti-counterfeiting requirements. In order to prevent the circulation of counterfeit and shoddy products, optical anti-counterfeiting technology has been widely used as an effective anti-counterfeiting method.

[0003] Single-mode optical anti-counterfeiting, such as relying solely on the identification of the luminescent color (wavelength) of the material, is an anti-counterfeiting method that is easily cracked and copied. Combining two or more modes of anti-counterfeiting materials is very helpful in solving problems such as low single anti-counterfeiting levels. The Chinese patent application number CN118580705A proposes a dual anti-counterfeiting method of structural color anti-counterfeiting under natural light and fluorescent anti-counterfeiting under ultraviolet excitation, specifically using mesoporous silica to load halogen perovskite fluorescent particles. However, three different fluorescent particles need to be prepared. At the same time, the environmental stability of halogen perovskite is relatively poor, and there are strict requirements on the application environment, service life and life. The Chinese patent application number 118580706A discloses a dual-mode composite anti-counterfeiting coating. Oxide is used as a raw material, and a stable fluorescent powder is obtained after calcination. After curing with epoxy resin and curing agent, a composite anti-counterfeiting coating is obtained after spraying with pearlescent pigments. However, this dual-mode anti-counterfeiting still requires two different fluorescent materials, which on the one hand increases the cost and difficulty of preparation; on the other hand, in practical applications, the double-layer composite structure is easy to separate, further limiting its practical application.

[0004] Therefore, developing multi-mode anti-counterfeiting for a single material is an urgent issue to be solved in current practical applications. Summary of the invention

[0005] In the field of anti-counterfeiting technology, existing optical anti-counterfeiting materials often rely on a single anti-counterfeiting mode, such as relying solely on the luminous color of the material for identification. This single anti-counterfeiting level is easy to imitate and copy, thereby reducing the anti-counterfeiting effect. In addition, existing anti-counterfeiting materials may have problems such as insufficient stability, low luminous efficiency, non-adjustable shape, or environmental unfriendliness. Therefore, the development of a new anti-counterfeiting material that can combine multiple anti-counterfeiting modes, improve stability and luminous efficiency, and is shape-adjustable and environmentally friendly has become a technical problem that needs to be solved in the field of anti-counterfeiting technology.

[0006] The purpose of the present invention is to provide a stable optical anti-counterfeiting material. This single material has four anti-counterfeiting modes, solving the current technical problem that multi-mode anti-counterfeiting requires the combination of at least two types of materials.

[0007] The present invention provides a four-mode anti-counterfeit glass, wherein the molar proportions of the components of the four-mode anti-counterfeit glass are respectively: SiO2: 30-60 mol%, Na2CO3: 5-20 mol%, Al2O3: 5-30 mol%, CaCO3: 3-10 mol%, NaF: 3-20 mol%, LuF3: 3-20 mol%, and EuF3: 0-5 mol%.

[0008] In the above scheme, the four-mode anti-counterfeiting glass has four different anti-counterfeiting modes, namely, utilizing fluorescent luminous color, long afterglow luminous color, light stimulation to restore long afterglow, and heat stimulation to restore long afterglow.

[0009] In the above scheme, the four-mode anti-counterfeit glass is made of Eu 2+ / Eu 3+ The luminous center.

[0010] In the above scheme, the four-mode anti-counterfeiting glass is treated with a reducing agent or a reducing atmosphere to remove Eu 3+ Partially reduced to Eu 2+ , forming Eu 2+ / Eu 3+ Luminous center.

[0011] The present invention also provides a method for preparing four-mode anti-counterfeit glass, comprising the following steps:

[0012] S1. Accurately weigh the raw materials and mix them thoroughly to obtain a mixed powder I;

[0013] S2. Weigh an appropriate amount of reducing agent powder, add it to the mixed powder I, and mix thoroughly to obtain a mixed powder II;

[0014] S3. The mixed powder II is transferred to a high temperature furnace, the furnace temperature is maintained at a temperature a1, and the temperature is kept for a period of time b1 until the mixed powder is completely melted;

[0015] S4. The melt is poured onto a mold at a temperature of a2, and a flat mold at a temperature of a2 is used above to apply stress to the melt to obtain a quenched glass I;

[0016] S5. After cutting and polishing glass I, transfer it to a low-temperature furnace with a temperature of a3 and keep it warm for a period of time b2 to obtain glass II, thus obtaining four-mode anti-counterfeiting glass.

[0017] In the above scheme, the reducing agent powder includes but is not limited to Al powder and reducing carbon powder, and the added amount of the reducing agent is ≤10 mol%.

[0018] In the above scheme, temperature a1 is 1200-1550°C, temperature a2 is 200-400°C, temperature a3 is 200-400°C, time b1 is 1-2 hours, and time b2 is 4-48 hours.

[0019] The present invention also provides a method for preparing four-mode anti-counterfeit glass, comprising the following steps:

[0020] S1. Accurately weigh the raw materials and mix them thoroughly to obtain a mixed powder I;

[0021] S2. The mixed powder I is transferred to a high temperature furnace, the furnace temperature is maintained at a temperature a4, and kept warm for a period of time b3 until the mixed powder is completely melted;

[0022] S3. The melt is poured onto a mold at a temperature of a5, and a flat mold at a temperature of a5 is used to apply stress to the melt to obtain quenched glass III;

[0023] S4. After cutting and polishing glass III, it is transferred to a low-temperature furnace, the furnace temperature is a6, and kept warm for a period of time b4 to obtain glass IV;

[0024] Four-mode anti-counterfeit glass made with S5-1 or S5-2:

[0025] S5-1. The glass IV is placed in a tube furnace and passed through a N2 / H2 mixture, the furnace temperature a7, and kept warm for a period of time b5 to obtain glass V, that is, four-mode anti-counterfeit glass;

[0026] S5-2. Place glass IV in step S4 in a crucible box with a lid, fill reducing agent powder around the glass, place the crucible box in a low-temperature furnace with a furnace temperature of a8, and keep it warm for a period of time b6 to obtain glass VI, that is, obtain four-mode anti-counterfeiting glass.

[0027] In the above scheme, temperature a4 is 1200-1550°C, temperature a5 is 200-400°C, temperature a6 is 200-400°C, and temperatures a7 and a8 are 300-400°C.

[0028] In the above scheme, time b3 is 1 to 2 hours, time b4 is 4 to 48 hours, and time b5 and b6 are 8 to 48 hours.

[0029] In the above scheme, Eu 3+ Partially reduced to Eu 2+ , forming Eu 2+ / Eu 3+ Luminous center.

[0030] Because the present invention adopts the above technical solution, it has the following beneficial effects:

[0031] First, a single material realizes four modes of optical anti-counterfeiting technology. Compared with single optical anti-counterfeiting, multi-mode optical anti-counterfeiting has a higher security level and is more difficult to crack and copy. However, the current multi-mode anti-counterfeiting requires at least two fluorescent materials to be combined to achieve it. The glass in the present invention has four different optical anti-counterfeiting modes at the same time, which is more practical.

[0032] Second, stability and cost. In terms of stability, on the one hand, the selected glass matrix has the characteristics of resistance to water, oxygen, high-energy radiation, heat, etc., and has high stability. On the other hand, the glass protects the luminescent center. After high-temperature heat treatment, the thermal stability of the anti-counterfeiting glass is more outstanding. In terms of cost and cycle, the raw material cost used in the present invention is low, the preparation method is simple and the cycle is short. Unlike phosphors, four-mode anti-counterfeiting glass does not require additional packaging. The glass preparation method and heat treatment method used in the present invention are based on mature glass preparation process technology and are very suitable for industrial production. Compared with powdered phosphors, the present invention is a block solid, which is easy to recycle and process, and is environmentally friendly, in line with national policies, and easy to promote and use.

[0033] Third, the luminescent center of the scintillator of the present invention is Eu 2+ / Eu 3+ On the one hand, Eu ions have very high luminescence efficiency and can fully match commercial Si and semiconductor detectors.

[0034] Fourthly, the four-mode anti-counterfeit glass of the present invention can be processed into a desired shape according to the application scenario, and has great flexibility.

[0035] Fifth, the present invention provides a composition ratio of the glass matrix, which can optimize the luminescent properties and provide a technical control method for industrial production and application.

[0036] The present invention provides a method for realizing Eu 2+ The present invention also provides a reducing agent addition amount control strategy, which helps to optimize Eu 2+ Concentration, adjust the emission wavelength.

[0037] The present invention also provides the melting temperature and subsequent heat treatment temperature of the four-mode anti-counterfeiting glass, which can optimize and regulate the luminescence performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is the X-ray diffraction pattern of Example 1-5 of the present invention.

[0039] Figure 2 This is the excitation spectrum of Example 1-2 of the present invention.

[0040] Figure 3 This is the emission spectrum of Example 1-2 of the present invention.

[0041] Figure 4 This is the excitation spectrum of embodiments 3-4 of the present invention.

[0042] Figure 5 Emission spectra of embodiments 3-4 of the present invention.

[0043] Figure 6 1 is the photoluminescence spectrum of Example 1 of the present invention at different excitation wavelengths.

[0044] Figure 7 The thermoluminescence spectra of Examples 1 and 3 of the present invention.

[0045] Figure 8 This is the long afterglow spectrum of Example 1 and Example 3 of the present invention.

[0046] Fig. 9 These are the corresponding luminescence images after the mold is filled in the embodiment, the long afterglow image, the photo of the complete attenuation of the afterglow after 5 minutes, the afterglow luminescence image restored by 980nm laser, and the afterglow luminescence image restored under thermal stimulation.

[0047] Fig.10 It is the time@temperature information encryption mode. DETAILED DESCRIPTION

[0048] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0049] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0050] The present invention provides a four-mode anti-counterfeit glass, wherein the molar ratio of the components of the four-mode anti-counterfeit glass is:

[0051] SiO2: 30~60mol%; Na2CO3: 5~20mol%; Al2O3: 5~30mol%; CaCO3: 3~10mol%; NaF: 3~20mol%; LuF3: 3~20mol%; EuF3: 0~5mol%;

[0052] Preferred glass component 1: SiO2: 45 mol%, Na2CO3: 10 mol%, Al2O3: preferably 15 mol%, CaCO3: 10 mol%, NaF: 5 mol%, LuF3: 8 mol%, EuF3: 2 mol%;

[0053] Preferred glass component 2: SiO2: 55 mol%, Na2CO3: 12 mol%, Al2O3: 8 mol%, CaCO3: 4 mol%, NaF: 13 mol%, LuF3: 4 mol%, EuF3: 4 mol%;

[0054] In the above scheme, the four-mode anti-counterfeiting glass has four different anti-counterfeiting modes, namely, utilizing fluorescent luminous color, long afterglow luminous color, light stimulation to restore long afterglow, and heat stimulation to restore long afterglow.

[0055] In the above scheme, the four-mode anti-counterfeit glass is made of Eu 2+ / Eu 3+ The luminous center.

[0056] In the above scheme, the four-mode anti-counterfeiting glass is treated with a reducing agent or a reducing atmosphere to remove Eu 3+ Partially reduced to Eu 2+ , forming Eu 2+ / Eu 3+ Luminous center.

[0057] The present invention also provides a method for preparing four-mode anti-counterfeit glass, comprising the following steps:

[0058] S1. Accurately weigh the raw materials and mix them thoroughly to obtain a mixed powder I;

[0059] S2. Weigh an appropriate amount of reducing agent powder, add it to the mixed powder I, and mix thoroughly to obtain a mixed powder II;

[0060] S3. The mixed powder II is transferred to a high temperature furnace, the furnace temperature is maintained at temperature a1, and the mixture is kept warm for a period of time b1 until the mixed powder is completely melted; wherein the temperature a1 is 1200-1550°C, and can be 1200°C, 1420°C, 1550°C, and the time b1 is 1 to 2 hours, and can be 1 hour or 2 hours;

[0061] S4. The melt is poured onto a mold at a temperature of a2, and a flat mold at a temperature of a2 is used to apply stress to the melt to obtain a quenched glass I; wherein the temperature a2 is 200-400°C, and may be 200°C, 300°C, or 400°C;

[0062] S5. After cutting and polishing glass I, transfer it to a low-temperature furnace, the temperature in the furnace is a3, and keep it warm for a period of time b2 to obtain glass II, and obtain four-mode anti-counterfeit glass. The temperature a3 is 200-400℃, which can be 200℃, 300℃, 600℃; the time b2 is 4-48 hours, which can be 4, 24, 48 hours;

[0063] In the above scheme, the reducing agent powder includes but is not limited to Al powder and reducing carbon powder, and the added amount of the reducing agent is ≤10 mol%, and 3 mol% may be selected.

[0064] The present invention also provides a method for preparing four-mode anti-counterfeit glass, comprising the following steps:

[0065] S1. Accurately weigh the raw materials and mix them thoroughly to obtain a mixed powder I;

[0066] S2. The mixed powder I is transferred to a high temperature furnace, the furnace temperature is maintained at a temperature a4, and the mixture is kept warm for a period of time b3 until the mixed powder is completely melted; wherein the temperature a4 is 1200-1550°C, which may be 1200°C, 1420°C, 1550°C, and the time b3 is 1 to 2 hours, which may be 1 hour or 2 hours;

[0067] S3. The melt is poured onto a mold at a temperature of a5, and a flat mold at a temperature of a5 is used to apply stress to the melt to obtain quenched glass III; wherein the temperature a5 is 200-400°C, which may be 200°C, 300°C, or 400°C;

[0068] S4. After cutting and polishing glass III, it is transferred to a low-temperature furnace, the furnace temperature a6, and kept warm for a period of time b4 to obtain glass IV; wherein the temperature a6 is 200-400 ℃, which can be 200 ℃, 400, 600 ℃; the time b4 is 4 to 48 hours, which can be 4, 12, 48 hours;

[0069] Four-mode anti-counterfeit glass made with S5-1 or S5-2:

[0070] S5-1. The glass IV is placed in a tubular furnace and passed through a N2 / H2 mixture, the furnace temperature a7, and kept warm for a period of time b5 to obtain a glass V, that is, a four-mode anti-counterfeit glass; the temperature a7 is 300-400 ℃, which can be 300 ℃, 400 ℃, and the time b5 is 8 to 48 hours, which can be 8 hours, 12 hours, 48 ​​hours;

[0071] S5-2. Put glass IV in step S4 into a crucible box with a lid, fill reducing agent powder around the glass, put the crucible box into a low-temperature furnace, the temperature in the furnace is a8, keep it warm for a period of time b6, and obtain glass VI, that is, obtain four-mode anti-counterfeit glass. The temperature a8 is 300-400℃, which can be 300℃ or 400℃, and the time b6 is 8-48 hours, which can be 8, 12, or 48 hours;

[0072] In the above scheme, Eu 3+ Partially reduced to Eu 2+ , forming Eu 2+ / Eu 3+ Luminous center.

[0073] Example 1

[0074] (1) accurately weigh the raw materials according to SiO2: 45 mol%, Na2CO3: 10 mol%, Al2O3: 15 mol%, CaCO3: 10 mol%, NaF: 7 mol%, LuF3: 8 mol%, EuF3: 2 mol%; Al: 3 mol%, mix them thoroughly, and transfer them into a crucible;

[0075] (2) transferring the crucible to a high-temperature furnace, maintaining the furnace temperature at 1420° C. for 1 hour, until the mixed powder in the crucible is completely molten;

[0076] (3) pouring the above molten liquid onto a mold at 300° C., and applying pressure to the glass liquid poured onto the mold using an iron plate at 300° C. to quench the molten liquid into glass;

[0077] (4) The glass obtained above is quickly transferred to an annealing furnace for annealing. The temperature of the annealing furnace is set at 300° C. for 24 hours. After naturally cooling to room temperature, the glass is cut and polished to obtain a four-mode anti-counterfeit glass.

[0078] Example 2

[0079] (1) accurately weighing raw materials according to SiO2: 45 mol%, Na2CO3: 10 mol%, Al2O3: 18 mol%, CaCO3: 10 mol%, NaF: 7 mol%, LuF3: 8 mol%, and EuF3: 2 mol%, and transferring them into a crucible after fully mixing them;

[0080] (2) transferring the crucible to a high-temperature furnace, maintaining the furnace temperature at 1420° C. for 1 hour, until the mixed powder in the crucible is completely molten;

[0081] (3) pouring the above molten liquid onto a mold at 300° C., and applying pressure to the glass liquid poured onto the mold using an iron plate at 300° C. to quench the molten liquid into glass;

[0082] (4) quickly transferring the glass obtained above into an annealing furnace, and annealing the glass above, wherein the temperature of the annealing furnace is set at 400° C. and the annealing time is 4 hours;

[0083] (5) After cutting and polishing, the glass is transferred to a tube furnace, the temperature of which is set at 400°C, and a N2 / H2 mixed gas is introduced at a flow rate of 100 sccm for 12 hours. After cooling naturally to room temperature, a four-mode anti-counterfeit glass is obtained.

[0084] Example 3

[0085] (1) accurately weigh the raw materials according to SiO2: 45 mol%, Na2CO3: 10 mol%, Al2O3: 15 mol%, CaCO3: 10 mol%, NaF: 5 mol%, LuF3: 8 mol%, EuF3: 2 mol%; carbon powder: 5 mol%, mix them thoroughly, and transfer them into a crucible;

[0086] (2) transferring the crucible to a high-temperature furnace, maintaining the furnace temperature at 1420° C. for 1 hour, until the mixed powder in the crucible is completely molten;

[0087] (3) pouring the above molten liquid onto a mold at 300° C., and applying pressure to the glass liquid poured onto the mold using an iron plate at 300° C. to quench the molten liquid into glass;

[0088] (4) The glass obtained above is quickly transferred to an annealing furnace for annealing. The temperature of the annealing furnace is set at 300° C. for 24 hours. After naturally cooling to room temperature, the glass is cut and polished to obtain a four-mode anti-counterfeit glass.

[0089] Example 4

[0090] (1) accurately weighing raw materials according to SiO2: 45 mol%, Na2CO3: 10 mol%, Al2O3: 18 mol%, CaCO3: 10 mol%, NaF: 7 mol%, LuF3: 8 mol%, and EuF3: 2 mol%, and transferring them into a crucible after fully mixing them;

[0091] (2) transferring the crucible to a high-temperature furnace, maintaining the furnace temperature at 1420° C. for 1 hour, until the mixed powder in the crucible is completely molten;

[0092] (3) pouring the above molten liquid onto a mold at 300° C., and applying pressure to the glass liquid poured onto the mold using an iron plate at 300° C. to quench the molten liquid into glass;

[0093] (4) quickly transferring the glass obtained above into an annealing furnace, and annealing the glass above, wherein the temperature of the annealing furnace is set at 400° C. and the annealing time is 4 hours;

[0094] (5) After cutting and polishing, the glass is transferred to a crucible with a lid, carbon powder is spread around the glass, and the crucible is transferred to a low-temperature furnace, the temperature of the furnace is set to 400°C, and the temperature is kept constant for 12 hours. After cooling naturally to room temperature, a four-mode anti-counterfeiting glass is obtained.

[0095] Example 5

[0096] (1) accurately weigh the raw materials according to SiO2: 55 mol%, Na2CO3: 12 mol%, Al2O3: 8 mol%, CaCO3: 4 mol%, NaF: 13 mol%, LuF3: 4 mol%, EuF3: 4 mol%; Al: 3 mol%, mix them thoroughly, and transfer them into a crucible;

[0097] (2) transferring the crucible to a high-temperature furnace, maintaining the furnace temperature at 1420° C. for 1 hour, until the mixed powder in the crucible is completely molten;

[0098] (3) pouring the above molten liquid onto a mold at 300° C., and applying pressure to the glass liquid poured onto the mold using an iron plate at 300° C. to quench the molten liquid into glass;

[0099] (4) The glass obtained above is quickly transferred to an annealing furnace for annealing. The temperature of the annealing furnace is set at 300° C. for 24 hours. After naturally cooling to room temperature, the glass is cut and polished to obtain a four-mode anti-counterfeit glass.

[0100] Figure 1 : This is the XRD spectrum of the anti-counterfeit glass samples obtained in Examples 1 to 4. The XRD spectrum of all samples obtained in Examples 1 to 4 only shows diffuse peaks without sharp diffraction peaks, indicating that all the obtained glass samples do not contain nanocrystals, and no new phase is generated even after subsequent heat treatment and the addition of Al powder.

[0101] Figure 2 The Eu of the glass sample obtained in Example 1-2 3+ The excitation spectrum of the monitored emission light is 615nm, which is a typical Eu 3+ The excitation spectrum has several wavelengths in the range of 300-550nm that are similar to Eu 3+The peaks are related to the 4f-4f transition of 7 F0→ 5 The luminescence peak of L6 is the strongest, while the broad peak between 250-320nm belongs to O 2- -Eu 3+ Charge transfer band. Figure 3 is Eu of the glass sample of Example 1-2 2+ The emission spectrum of the 250-425nm strong excitation band comes from Eu 2+ of 4 f7→ 4 f6 5 d1 transition. This indicates that the glass sample obtained contains Eu 2+ / Eu 3+ The luminous center.

[0102] Figure 4 is the Eu of the glass sample obtained in Example 3-4 3+ The emission light monitored is 616 nm, which is typical of Eu 3+ The glow. Figure 5 is Eu of the glass sample of Example 3-4 2+ Similar to using A1 powder as a reducing agent, using carbon powder as a reducing agent also yields the emission spectrum of Eu 2+ / Eu 3+ Glass sample with luminescent center.

[0103] Figure 6 This is the photoluminescence spectrum of Example 1. When the glass sample is excited by 383nm light, the glass mainly emits light at 460nm, while when the glass sample is excited by 394nm light, it emits light at 615nm. In addition, the luminescence peak of the glass will shift greatly depending on the amount of reducing agent added. Under fluorescent light, the glass is colorless, but when using ultraviolet laser, the glass shows different colors. In practical applications, the authenticity can be identified based on the color.

[0104] Figure 7 The thermoluminescence curve of the sample in Example 1 is shown in Figure 2. The sample was first heated for a sufficient time to clear the trapped electrons, and then excited with 365nm ultraviolet light for 2 minutes. The thermoluminescence result at a heating rate of 1°C / s is shown in Figure 2. Figure 7 The thermoluminescence curve of the sample in Example 3 is a smooth straight line, indicating that there is no obvious thermoluminescence phenomenon in the glass during the heating process.

[0105] Figure 8The long afterglow spectra of Examples 1 and 3 are shown in Figure 1. After 5 minutes of excitation with 365nm violet light, the sample in Example 1 exhibits long afterglow luminescence, while no long afterglow luminescence is observed in the sample in Example 3. This indicates that the sample exhibits long afterglow luminescence due to the presence of the reducing agent.

[0106] Fig. 9 The corresponding luminescence image after filling the mold in the embodiment, the long afterglow image, the photo of the complete attenuation of the afterglow after 5 minutes, the afterglow luminescence image restored by 980nm laser and the afterglow luminescence image restored under thermal stimulation. Under fluorescent light, "ZJ" is colorless, but under ultraviolet light excitation, "Z (sample of Example 1)" shows cyan, and "J (sample of Example 2)" shows light blue. After turning off the light, "Z" and "J" emit long afterglow, and the afterglow disappears after 5 minutes. After irradiation with 980nm laser, the long afterglow can be seen to be restored. In addition, the long afterglow luminescence can also be restored under thermal stimulation of 50, 100, and 150°C. The above changes can be used in the field of anti-counterfeiting.

[0107] Fig.10 It is the time@temperature information encryption mode. After being irradiated by UV light, different information can be read out under different external conditions. For example, after 30s at 30℃ (30s@30℃, named (30,30)), only "Z" is read out, while "Z" and "J" can be read out at the coordinates of (0,200). And the contrast between "Z" and "J" is different at different coordinates.

Claims

1. A four-mode anti-counterfeit glass, characterized in that: The molar proportions of the components of the four-mode anti-counterfeit glass are: SiO2: 30-60 mol%, Na2CO3: 5-20 mol%, Al2O3: 5-30 mol%, CaCO3: 3-10 mol%, NaF: 3-20 mol%, LuF3: 3-20 mol%, EuF3: 0-5 mol%.

2. The four-mode anti-counterfeit glass according to claim 1, characterized in that: The four-mode anti-counterfeiting glass has four different anti-counterfeiting modes: fluorescent luminous color, long afterglow luminous color, light stimulation to restore long afterglow and heat stimulation to restore long afterglow.

3. The four-mode anti-counterfeit glass according to claim 1, characterized in that: The four-mode anti-counterfeiting glass is made of Eu 2+ / Eu 3+ The luminous center.

4. The four-mode anti-counterfeit glass according to claim 1, characterized in that: The four-mode anti-counterfeiting glass is treated with a reducing agent or a reducing atmosphere to 3+ Partially reduced to Eu 2+ , forming Eu 2+ / Eu 3+ Luminous center.

5. The method for preparing the four-mode anti-counterfeit glass according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Accurately weigh the raw materials and mix them thoroughly to obtain a mixed powder I; S2. Weigh an appropriate amount of reducing agent powder, add it to the mixed powder I, and mix thoroughly to obtain a mixed powder II; S3. The mixed powder II is transferred to a high temperature furnace, the furnace temperature is maintained at a temperature a1, and the temperature is kept for a period of time b1 until the mixed powder is completely melted; S4. The melt is poured onto a mold at a temperature of a2, and a flat mold at a temperature of a2 is used above to apply stress to the melt to obtain a quenched glass I; S5. After cutting and polishing glass I, transfer it to a low-temperature furnace with a temperature of a3 and keep it warm for a period of time b2 to obtain glass II, thus obtaining four-mode anti-counterfeiting glass.

6. The preparation method according to claim 5, characterized in that: The reducing agent powder includes but is not limited to Al powder and reducing carbon powder, and the adding amount of the reducing agent is ≤10 mol%.

7. The preparation method according to claim 5, characterized in that: The temperature a1 is 1200-1550°C, the temperature a2 is 200-400°C, the temperature a3 is 200-400°C, the time b1 is 1-2 hours, and the time b2 is 4-48 hours.

8. The method for preparing the four-mode anti-counterfeit glass according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Accurately weigh the raw materials and mix them thoroughly to obtain a mixed powder I; S2. The mixed powder I is transferred to a high temperature furnace, the furnace temperature is maintained at a temperature a4, and kept warm for a period of time b3 until the mixed powder is completely melted; S3. The melt is poured onto a mold at a temperature of a5, and a flat mold at a temperature of a5 is used to apply stress to the melt to obtain quenched glass III; S4. After cutting and polishing glass III, it is transferred to a low-temperature furnace, the furnace temperature is a6, and kept warm for a period of time b4 to obtain glass IV; Four-mode anti-counterfeit glass made with S5-1 or S5-2: S5-1. The glass IV is placed in a tube furnace and passed through a N2 / H2 mixture, the furnace temperature a7, and kept warm for a period of time b5 to obtain glass V, that is, four-mode anti-counterfeit glass; S5-2. Place glass IV in step S4 in a crucible box with a lid, fill reducing agent powder around the glass, place the crucible box in a low-temperature furnace with a furnace temperature of a8, and keep it warm for a period of time b6 to obtain glass VI, that is, obtain four-mode anti-counterfeiting glass.

9. The preparation method according to claim 8, characterized in that: Temperature a4 is 1200-1550°C, temperature a5 is 200-400°C, temperature a6 is 200-400°C, and temperatures a7 and a8 are 300-400°C.

10. The preparation method according to claim 8, characterized in that: The time b3 is 1 to 2 hours, the time b4 is 4 to 48 hours, and the times b5 and b6 are 8 to 48 hours.

Citation Information

Patent Citations

  • Eu&lt;3+&gt;Dy&lt;3+&gt; / Gd&lt;3+&gt; triple-doped Na5Lu9F32 monocrystal and growth method thereof

    CN105780116A

  • Silicate activated based on divalent europium ions and trivalent europium ions and preparation method and application thereof

    CN113046065A

  • Neutral borosilicate glass medicinal tube with anti-counterfeiting function and preparation method thereof

    CN115073014A

  • Borate based on co-activation of divalent europium ions and trivalent europium ions as well as preparation method and application of borate

    CN115074127A

  • Non-lead glass ceramic scintillator and preparation method and application thereof

    CN117361887A